A Neoliberal Rentier System: New Challenges and Past Economic Trajectories in Iraq. Issue 1 (2nd January 2017) - Costantini, Irene
ABSTRACT: The Islamic State's conquest of swathes of Iraqi territory, combined with falling oil prices, revealed the fault lines of a model of economic development that made the country extremely vulnerable to the events of 2014. Over the last 13 years, the consolidation of the rentier economy in parallel to the promotion of a neoliberal model – a neoliberal rentier system – has not initiated a process of sustainable economic development. The main factors explaining this missed opportunity can be found in the tensions that exist between the two models and, in particular, between the relative roles of the state and the private sector as drivers of economic development.